Antibody and T-Cell Responses 6 Months After Coronavirus Disease 2019 Messenger RNA-1273 Vaccination in Patients With Chronic Kidney Disease, on Dialysis, or Living With a Kidney Transplant. (9th August 2022) - Sanders, Jan-Stephan F; Messchendorp, A Lianne; de Vries, Rory D; Baan, Carla C; van Baarle, Debbie; van Binnendijk, Rob; Diavatopoulos, Dimitri A; Geers, Daryl; Schmitz, Katharina S; GeurtsvanKessel, Corine H; den Hartog, Gerco; Kho, Marcia M L; et al.
Abstract: Background: The immune response to COVID-19 vaccination is inferior in kidney transplant recipients (KTRs) and to a lesser extent in patients on dialysis or with chronic kidney disease (CKD). We assessed the immune response 6 months after mRNA-1273 vaccination in kidney patients and compared this to controls. Methods: A total of 152 participants with CKD stages G4/5 (eGFR <30 mL/min/1.73 m 2 ), 145 participants on dialysis, 267 KTRs, and 181 controls were included. SARS-CoV-2 Spike S1 specific IgG antibodies were measured using fluorescent bead-based multiplex-immunoassay, neutralizing antibodies to ancestral, Delta, and Omicron (BA.1) variants by plaque reduction, and T-cell responses by interferon- γ release assay. Results: At 6 months after vaccination, S1-specific antibodies were detected in 100% of controls, 98.7% of CKD G4/5 patients, 95.1% of dialysis patients, and 56.6% of KTRs. These figures were comparable to the response rates at 28 days, but antibody levels waned significantly. Neutralization of the ancestral and Delta variants was detected in most participants, whereas neutralization of Omicron was mostly absent. S-specific T-cell responses were detected at 6 months in 75.0% of controls, 69.4% of CKD G4/5 patients, 52.6% of dialysis patients, and 12.9% of KTRs. T-cell responses at 6 months were significantly lower than responses at 28 days. Conclusions: Although seropositivity rates at 6 months were comparable to rates at 28 days after vaccination, significantly decreased antibody levels and T-cell responses were observed. The combination of low antibody levels, reduced T-cell responses, and absent neutralization of the newly emerging variants indicates the need for additional boosts or alternative vaccination strategies in KTRs. Clinical Trials Registration: NCT04741386. Abstract : Antibodies and T cells became undetectable in substantial proportions of dialysis and kidney transplant patients at 6 months after coronavirus disease 2019 messenger RNA-1273 vaccination and were also lower in chronic kidney disease patients than in controls. The slopes of these decreases in vaccine-induced immunity were similar among patient groups and controls. Neutralizing antibodies to the Omicron variant were barely detectable.